2021
DOI: 10.15420/aer.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Convergent Procedure for the Treatment of Persistent and Long-standing Persistent Atrial Fibrillation

Abstract: Recent advances have been made in AF treatment, including the role of early rhythm control and landmark clinical trials using ablation therapy. However, some treatment gaps remain, including the creation of durable lesions outside the pulmonary veins and effective treatment of longstanding persistent AF. A novel epicardial-endocardial ablation approach – the hybrid convergent procedure – was developed to combine surgical and catheter ablation techniques into a collaborative, multidisciplinary approach to manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(118 citation statements)
references
References 56 publications
5
112
1
Order By: Relevance
“…Our stepwise endo‐/epicardial approach differs in several ways from previously described hybrid techniques for AF CA 24,25 . Although we gained access to the pericardial space with a small subxiphoid pericardial window, we did not navigate the pericardium under direct vision, and all ablation lesions were delivered by the electrophysiologist using conventional ablation catheters, therefore limiting the need for assistance by the cardiac surgeon to the initial and terminal moments of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our stepwise endo‐/epicardial approach differs in several ways from previously described hybrid techniques for AF CA 24,25 . Although we gained access to the pericardial space with a small subxiphoid pericardial window, we did not navigate the pericardium under direct vision, and all ablation lesions were delivered by the electrophysiologist using conventional ablation catheters, therefore limiting the need for assistance by the cardiac surgeon to the initial and terminal moments of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In the multicenter, randomized Convergence of Epicardial and Endocardial Ablation for the Treatment of Symptomatic Persistent AF (CONVERGE) trial, 150 patients with persistent and long-standing persistent AF were assigned in a 2:1 randomized manner to hybrid convergent ablation approach and catheter ablation. 23 The hybrid group underwent epicardial ablation using a vacuum-assisted, unipolar radiofrequency ablation introduced via a subxiphoid/ transdiaphragmatic approach followed by endocardial catheter ablation. The catheter ablation group underwent PVI with a roof line and cavotricuspid isthmus ablation line.…”
Section: Ablation Strategies: Convergent Approachmentioning
confidence: 99%
“…[80][81][82][83][84][85] Stand-alone surgical AF ablation continues to have a role in patients who have symptomatic AF that is refractory to AAD and catheter ablation (class IIA, LOE B), especially as a "hybrid" procedure. 80,86,87 Prior data have shown that larger LA size and longer duration of preoperative AF, both of which are linked to more advanced ACM, are predictors of persistent AF after surgical maze procedure. [88][89][90] Although surgical ablation has been found to be efficacious in restoring sinus rhythm, the available data to demonstrate a link between LA reverse remodeling parameters and longterm freedom from recurrent AF in those who underwent surgical ablation are overall limited.…”
Section: Acm Catheter Ablation and Af Ablation Surgerymentioning
confidence: 99%
“…Per the Society of Thoracic Surgeons clinical practice guidelines, surgical ablation for AF is a class I recommendation when performed at the time of concomitant cardiac surgery, such as coronary artery bypass or valve surgery, and several reports document improved survival compared to patients undergoing concomitant surgery without AF treatment 80–85 . Stand‐alone surgical AF ablation continues to have a role in patients who have symptomatic AF that is refractory to AAD and catheter ablation (class IIA, LOE B), especially as a “hybrid” procedure 80,86,87 . Prior data have shown that larger LA size and longer duration of preoperative AF, both of which are linked to more advanced ACM, are predictors of persistent AF after surgical maze procedure 88–90 .…”
Section: Acm Catheter Ablation and Af Ablation Surgerymentioning
confidence: 99%